Emerging voices in ICT and agriculture / Voix nouvelles des TIC et de l'agriculture - Bellinzas, Giorgio; Matturi, Jenessi; Lohento, Ken (Technical Centre for Agricultural and Rural Cooperation, 2013)
The ARDYIS (Agriculture, Rural Development and Youth in the Information Society) project is one of CTA’s recent initiatives with ACP partners, notably created to improve ICT access for rural youth. Its aim is to raise awareness and strengthen the capacity of young people, allowing them to contribute to agriculture and rural development through the use of ICTs. This booklet provides an overview and the results of the essay competition «Youth finding solutions to challenges in agriculture and rural development using ICTs! », one of the many ARDYIS activities. Entries submitted demonstrated that youth are more and more interested in the agricultural sector and supporting them will definitely have a strong impact in attracting more youth to rural areas. /